A magnesium ion-enriched framework layered double hydroxide material, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611221665.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有LDH材料的镁离子负载量低,同时材料在结构适配性与力学性能调控上存在显著局限:其固有形貌设计缺乏对细胞接触行为的针对性优化,难以形成高效的细胞—材料相互作用界面,导致细胞与材料的关键接触过程受限;这些问题直接制约了促成骨效应的充分发挥,使得现有LDH材料的成骨分化的诱导效率不足,难以满足临床骨缺损修复的实际需求
1、本发明通过碱刻蚀法对传统LDH材料进行结构改造,成功制备了具有中空结构的独立六边形孔的MF-LDH材料,X射线光电子能谱表征结果显示,相比LDH,本发明制备得到的MF-LDH中镁离子与铝离子比例显著上调,达到Atomic %Mg:Atomic % Al=11.82,成功制备了镁离子富集的框架层状双金属氢氧化物材料MF-LDH,实现了镁离子的高效富集,有利于充分发挥镁离子在骨代谢和成骨分化中的调控作用。
Smart Images

Figure CN122977418A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical nanomaterials, and in particular to a magnesium ion-enriched framework layered bimetallic hydroxide material, its preparation method, and its applications. Background Technology
[0002] Bone defect repair is a major challenge in clinical medicine. Ideal bone repair materials need to possess excellent biocompatibility, controllable release of bioactive components, and highly efficient osteogenic differentiation induction activity. Magnesium ions, as an important component of human bone tissue, participate in key processes such as bone metabolism, cell proliferation and differentiation regulation, and hydroxyapatite crystal formation, playing a crucial role in the construction of the osteogenic microenvironment. Layered bimetallic hydroxides (LDHs) have attracted much attention in the field of biomaterials due to their tunable metal composition, good biocompatibility, and ion exchange capacity. However, existing LDH materials have low magnesium ion loading, and their structural adaptability and mechanical property control are significantly limited: their inherent morphology design lacks targeted optimization for cell contact behavior, making it difficult to form an efficient cell-material interaction interface, thus restricting key cell-material contact processes. These problems directly restrict the full realization of osteogenic effects, resulting in insufficient osteogenic differentiation induction efficiency of existing LDH materials, which fails to meet the actual needs of clinical bone defect repair.
[0003] Therefore, developing a magnesium ion-enriched framework layered double hydroxide (MF-LDH) material has significant application value in the field of bone repair. Summary of the Invention
[0004] To address the aforementioned issues, the present invention aims to provide a magnesium ion-enriched framework layered bimetallic hydroxide material, its preparation method and application, and its application in osteogenic differentiation. By regulating the material composition and structure, the bone repair effect is significantly enhanced.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention provides a magnesium ion-enriched framework layered bimetallic hydroxide material, wherein the framework layered bimetallic hydroxide material is a hollow crystalline material with independent hexagonal pores, and the morphology of the independent hexagonal pores is a single hexagonal unit in a honeycomb structure; the magnesium ion-enriched framework layered bimetallic hydroxide material is obtained by alkaline etching of conventional layered bimetallic hydroxides.
[0006] Furthermore, the general formula of the conventional nanolayered double hydroxide is [M 2+ (1-x) M3+ X [OH)2]x+[An-]x / n·zH2O, where M 2+ It is a divalent metal cation, M 3+ A is a trivalent metal cation. n- M is an anion with an interlayer valence of n, X is the molar ratio of trivalent cations to all cations, z is the number of water molecules of crystallization between each nanolayered double hydroxide molecule, and M is the anion with an interlayer valence of n. 2+ and M 3+ The salts formed are all soluble.
[0007] Furthermore, the M 2+ Mg 2+ The M 3+ For Al 3+ The A n- CO3 2- ; Mg in the material 2+ With Al 3+ The molar ratio is (1-x):x = 1:1 - 5:1.
[0008] The second aspect of this invention provides a specific method for preparing the above-mentioned magnesium ion-enriched framework layered bimetallic hydroxide material as follows: (1) Disperse traditional layered double hydroxide (LDH) materials in water to prepare an LDH suspension with a concentration of 1.0-2.5 mg / mL; (2) Prepare an alkaline solution of 0.5-2 mol / L using double-distilled water to remove CO2 as a solvent; (3) The LDH suspension obtained in step (1) and the alkaline solution are mixed at a ratio of 1.5-2 mg / mL between LDH and alkaline solution, and transferred to a hydrothermal synthesis reactor. The mixture is heated at 150-160℃ for 2-5 h to obtain the suspension. (4) After washing with deionized water three times, the suspension is then freeze-dried at -80°C or vacuum-dried at 37°C to obtain a magnesium ion-enriched framework layered bimetallic hydroxide material.
[0009] Further, the alkaline solution in step (3) is either a potassium hydroxide solution or a sodium hydroxide solution; the concentration of the alkaline solution is 1M.
[0010] Furthermore, the traditional method for preparing layered double hydroxide materials includes the following steps: S1. Dissolve soluble divalent metal ion salts and soluble trivalent metal ion salts in water to prepare metal ion salt solutions; S2. Use double-distilled water (with CO2 removed) as a solvent to prepare a urea solution; S3. Mix the metal ion salt solution and urea solution, transfer them to a hydrothermal synthesis reactor, and heat at 100°C for 24 hours to obtain a suspension; S4. Dry the suspension to obtain a traditional layered double hydroxide.
[0011] Further, in step S1, the soluble divalent metal ion salt is selected from either magnesium nitrate or magnesium chloride; the soluble trivalent metal ion salt is selected from either aluminum nitrate or aluminum chloride.
[0012] Furthermore, the molar ratio of the divalent metal ion salt to the trivalent metal ion salt in step S1 is 1:1 to 5:1.
[0013] Furthermore, in step S3, the molar ratio of urea to metal ion salt solution is 3 to 5:1.
[0014] A third aspect of the present invention provides the application of the above-mentioned magnesium ion-enriched framework layered bimetallic hydroxide material in the preparation of a drug that promotes osteogenic differentiation of mesenchymal stem cells.
[0015] Furthermore, the mesenchymal stem cells are bone marrow-derived mesenchymal stem cells or osteoblastic progenitor cells.
[0016] The fourth aspect of this invention provides the application of the above-mentioned magnesium ion-enriched framework layered bimetallic hydroxide material in the preparation of drugs for bone defect repair and regeneration.
[0017] Furthermore, the amount of magnesium ion-enriched framework layered bimetallic hydroxide material added to the drug is 5-30 μg / mL.
[0018] Compared with the prior art, the present invention has achieved the following beneficial technical effects: 1. This invention modifies the structure of traditional LDH materials using an alkaline etching method, successfully preparing MF-LDH materials with independent hexagonal pores and a hollow structure. X-ray photoelectron spectroscopy characterization results show that, compared with LDH, the ratio of magnesium ions to aluminum ions in the MF-LDH prepared by this invention is significantly increased, reaching Atomic %Mg: Atomic %Al = 11.82. This successfully prepares a magnesium ion-enriched framework layered bimetallic hydroxide material MF-LDH, achieving efficient enrichment of magnesium ions, which is beneficial for fully leveraging the regulatory role of magnesium ions in bone metabolism and osteogenic differentiation.
[0019] 2. This invention provides a magnesium ion-enriched framework-layered bimetallic hydroxide material for promoting osteogenic differentiation of mesenchymal stem cells. Cell viability assays, alkaline phosphatase staining and alizarin red staining after osteogenic differentiation, and real-time quantitative PCR detection of osteogenic differentiation gene expression all indicate that MF-LDH material intervention resulted in deeper alkaline phosphatase and alizarin red staining, and upregulated expression of osteogenic differentiation-related genes BMP2, RunX2, and OPN. Therefore, the magnesium ion-enriched framework-layered bimetallic hydroxide material can more effectively promote osteogenic differentiation of mesenchymal stem cells and has broad application prospects. Attached Figure Description
[0020] Figure 1 shows the scanning electron microscope (SEM) morphology of the nanomaterials LDH and MF-LDH in Example 1 of the present invention; wherein, Figures B, C, E, and F show the transmission electron microscope (TEM) morphology and corresponding elemental mapping analysis of the nanomaterials LDH and MF-LDH in Example 1 of the present invention; Figures G and H show the three-dimensional morphology of the nanomaterials LDH and MF-LDH in Example 1 of the present invention using atomic force microscopy; Figure I shows the X-ray photoelectron spectroscopy (XPS) characterization of the nanomaterials LDH and MF-LDH in Example 1 of the present invention; and Figure J shows the surface elemental composition of the MF-LDH material.
[0021] Figure 2 The results (CCK8) show the cytotoxicity of BMSCs treated with different concentrations of LDH and MF-LDH nanomaterials 48 h after treatment. The horizontal axis represents the concentration of each drug group, the vertical axis represents the cell survival rate of BMSCs, and the survival rate of the blank control group is set to 100%.
[0022] Figure 3 The images show the alkaline phosphatase staining results after 7 days and the alizarin red staining results after 14 days of MF-LDH treatment of BMSCs in the control group and Example 1 of this invention. Figure A shows the ALP staining results after 7 days of MF-LDH treatment of BMSCs in the control group and Example 1 of this invention, and Figure B shows the alizarin red staining results after 14 days of MF-LDH treatment of BMSCs in the control group and Example 1 of this invention. The control group shows the staining results of BMSCs differentiated by only osteogenic differentiation culture medium.
[0023] Figure 4 This is a bar chart showing the gene expression levels of osteogenic-related genes BMP2, RunX2, and OPN after 7 days of BMSC differentiation treated with the nanomaterial MF-LDH in Example 1 of this invention. The horizontal axis represents different material treatments, and the vertical axis represents the relative expression level. The relative expression level of the control group is set to 1.
[0024] Figure 5This is a scanning electron microscope image of the adhesion and spreading morphology of BMSC cells on the surface of the MF-LDH material. Detailed Implementation
[0025] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the technical solution of this invention is described in detail below. This invention is not limited to the specific embodiments listed below. Those skilled in the art can implement this invention using various other specific embodiments based on the content disclosed herein. Any modifications or variations made to the design structure and concept of this invention fall within the protection scope of this invention. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0026] Unless otherwise specified, the experimental methods in the following examples are conventional methods, and the experimental materials used are all commercially available products.
[0027] To make the technical means, creative features, objectives and effects of this invention easier to understand, the following describes in detail, with reference to embodiments and accompanying drawings, a method for preparing a nanocomposite material that promotes osteogenic differentiation of mesenchymal stem cells according to this invention.
[0028] Mesenchymal stem cells (MSCs) are a type of stem cell that can differentiate into adult cells such as bone, cartilage, and fat in different culture systems. They have advantages such as short experimental cycles, sensitive indicators, and ease of standardization in experimental research. In this invention, rat bone marrow-derived mesenchymal stem cells (BMSCs) are mainly used for experiments.
[0029] In the following examples, the BMSCs used were purchased from Guangzhou Cyagen Biosciences Co., Ltd.; the high-glucose DMEM, fetal bovine serum, and penicillin / streptomycin (double antibiotics) used were essential components of the cell culture medium for maintaining normal cell growth and were commercially available products purchased from Gibco, USA; the dexamethasone, sodium ascorbate, β-glycerophosphate, and 1,25-dihydroxyvitamin D3 used in the culture medium for osteogenic differentiation of BMSCs were purchased from Merck Sigma-Aldrich, Germany. Other non-self-made reagents and raw materials were generally commercially available products.
[0030] In the following examples, BMSCs were prepared by changing the metal ion composition based on nanolayered double hydroxides (LDH), and osteogenic differentiation was carried out on BMSCs treated with various LDH materials. The experimental results showed that various LDH materials had different degrees of effect on promoting osteogenic differentiation of BMSCs. The best material synthesis method is shown in Example 1, and other types of materials are shown in Examples 2-3.
[0031] The present invention will be further described in detail below with reference to the embodiments: Example 1: Preparation of nanolayered double hydroxide LDH and framework layered bimetallic hydroxide material MF-LDH The specific steps for preparing nanolayered double hydroxide LDH and framework layered bimetallic hydroxide material MF-LDH are as follows: (1) Prepare a 40 mL solution of a metal ion salt using 10 mmol magnesium nitrate and 2 mmol aluminum nitrate, wherein Mg 2+ With Al 3+ The molar ratio between them is 5:1.
[0032] (2) Using CO2-free ddH2O (double-distilled water) as a solvent, prepare 20 mL of 0.04 M urea solution. Mix 40 mL of the metal ion salt solution obtained in step (1) with 20 mL of the urea solution obtained in step (2), transfer to a hydrothermal synthesis reactor, and heat at 100 °C for 24 h to obtain the first suspension.
[0033] (3) The first suspension was dried in a vacuum drying oven at 37°C to obtain nano-layered double hydroxide LDH.
[0034] (4) Prepare 60 mL of alkaline solution using 60 mmol of potassium hydroxide.
[0035] (5) Take 0.1 g of the LDH obtained in step (3) and disperse it in 60 mL of the solution prepared in step (4). Transfer it to a hydrothermal synthesis reactor and heat it at 160℃ for 5 h to obtain the second suspension.
[0036] (6) The second suspension was dried in a vacuum drying oven at 37°C to obtain a framework layered bimetallic hydroxide material MF-LDH. The surface morphology of the LDH obtained in step (3) and the surface morphology of the MF-LDH obtained in step (6) were observed by scanning electron microscopy and transmission electron microscopy.
[0037] Figure 1 (AC) shows the scanning electron microscope (SEM) morphology, transmission electron microscope (TEM) morphology, and mapping elemental analysis of the nano-layered double hydroxide LDH in the embodiments of the present invention. As can be seen from Figure 1A-C, the nano-layered double hydroxide LDH has a good crystal structure, mostly hexagonal, with uniform morphology and size, and a particle size of about 3.8 µm.
[0038] Figure 1 (CE) shows the scanning electron microscope (SEM) and transmission electron microscope (TEM) morphologies of the framework layered bimetallic hydroxide material MF-LDH in the embodiments of the present invention. As can be seen from the figure, MF-LDH exhibits a crystal structure with independent hexagonal pores and a hollow structure, similar to a single hexagonal unit in a honeycomb structure. The morphology is uniform and the size is uniform, with a particle size of 3.8 µm.
[0039] Figures 1(G) and (H) show the three-dimensional morphological characterization of the nanomaterials LDH and MF-LDH in the embodiments of the present invention using atomic force microscopy. The figures show that the thickness of LDH is 200 nm and the thickness of MF-LDH is 54 nm, indicating that the material thickness is significantly thinned after etching.
[0040] Figure 1 (IJ) shows the X-ray photoelectron spectroscopy characterization of the nanomaterials LDH and MF-LDH in the embodiments of the present invention and the surface elemental composition of MF-LDH material. As can be seen from the figure, compared with LDH, the ratio of magnesium ions to aluminum ions in MF-LDH is significantly increased, reaching Atomic %Mg: Atomic %Al=11.82, and the magnesium ion-enriched framework layered bimetallic hydroxide material MF-LDH was successfully prepared.
[0041] Example 2 The difference from Example 1 is that the Mg in the metal ion salt solution prepared in step (1) is different. 2+ With Al 3+ The molar ratio between them was 3:1. The remaining operations were the same as in Example 1. The MF-LDH material was successfully obtained.
[0042] Example 3 The difference from Example 1 is that the Mg in the metal ion salt solution prepared in step (1) is different. 2+ With Al 3+ The molar ratio between them was 1:1. The remaining operations were the same as in Example 1. Ultimately, a hollow frame MF-LDH material was not successfully obtained.
[0043] Example 4: Cell viability assay (CCK) This embodiment examines the cytotoxicity of different concentrations of LDH and MF-LDH nanomaterials on BMSCs. The specific operational steps are as follows: Step 1: Culture rat bone marrow-derived mesenchymal stem cells (BMSCs).
[0044] BMSCs were seeded into 96-well plates at a density of 8000 cells / well and cultured in medium at 37°C and 5% CO2 for 18–24 h for subsequent material processing. The BMSC medium consisted of MEM and 10% fetal bovine serum. In this experiment, the culture time was 24 h.
[0045] Step 2: Prepare two sets of solutions using BMSC medium as the solvent. Each set of solutions is prepared with five concentrations: LDH solution and MF-LDH solution. The concentrations are 5 μg / mL, 10 μg / mL, 20 μg / mL, 40 μg / mL, and 80 μg / mL, respectively.
[0046] Step 3: Discard the supernatant from the cultured BMSCs in Step 1. Add different concentrations of LDH and MF-LDH solutions prepared in Step 2 to each well. After culturing for 48 h, add 20 μL of CCK8 solution to each well. After incubating in the dark for 4 h, measure the OD (optical density) value at 450 nm using a microplate reader. The formula is: Cell viability = (Experimental group OD value / (Experimental group OD value)) (OD value of blank group) / (OD value of control group) The cell viability of each group was calculated by multiplying the OD value of the blank group by 100% and correcting for the background absorbance of the blank group.
[0047] Figure 2 This is the cytotoxicity result (CCK8 assay) of BMSCs treated with different concentrations of LDH and MF-LDH nanomaterials in Example 1 of this invention after 48 h. The horizontal axis represents the drug concentration in each group, and the vertical axis represents the cell viability of BMSCs. The viability of the blank control group was set to 100%.
[0048] Depend on Figure 2 It was found that at concentrations of 5 μg / mL and 10 μg / mL, the cell viability after treatment with LDH and MF-LDH for 48 h was not significantly different from that of the blank control group. However, as the concentration increased to 20 μg / mL, the cell viability after treatment with LDH for 48 h decreased significantly, while the cell viability after treatment with MF-LDH for 48 h remained above 75% even at a material concentration as high as 80 μg / mL. This indicates that the MF-LDH group exhibits excellent biocompatibility, and treatment concentrations below 40 μg / mL have no effect on BMSC cell proliferation.
[0049] Example 5: Alkaline phosphatase and Alizarin Red staining during osteogenic differentiation 1. Alkaline phosphatase staining BMSCs were seeded in 12-well plates at a density of 1×10⁵ / mL and cultured in medium at 37℃ and 5% CO₂ for 18-24 h. Cells were used for subsequent material processing when the confluence density reached 70%. The composition of the BMSC osteogenic differentiation medium was: MEM; 10% fetal bovine serum; 0.1 μmol / L dexamethasone; 20 μg / mL sodium anticortiate; 10 Mm β-glycerophosphate. LDH and MF-LDH solutions were prepared using the BMSC osteogenic differentiation medium to achieve a material concentration of 5 µg / mL in each group. After 7 days of differentiation, the cells were fixed with 4% paraformaldehyde, and the osteogenic differentiation effect was assessed using alkaline phosphatase (ALP) activity.
[0050] Figure 3(A) shows the ALP staining of BMSCs treated with MF-LDH for 7 days in the control group (only osteogenic differentiation culture medium) and in Example 1 of this invention. As can be seen from the figure, morphologically, the treatment with MF-LDH can promote osteogenic differentiation of BMSCs, and the staining of alkaline phosphatase is darker than that in the control group, indicating that it enhances the effect of promoting osteogenic differentiation.
[0051] 2. Alizarin Red staining BMSCs were seeded in 12-well plates at a density of 1×10⁵ / mL and cultured in medium at 37℃ and 5% CO₂ for 18-24 h. Cells were used for subsequent material processing when the confluence density reached 70%. The composition of the BMSC osteogenic differentiation medium was: MEM; 10% fetal bovine serum; 0.1 μmol / L dexamethasone; 20 μg / mL sodium anticortiate; 10 mM β-glycerophosphate. LDH and MF-LDH solutions were prepared using the BMSC osteogenic differentiation medium to achieve a material concentration of 5 µg / mL in each group. After 14 days of differentiation, the cells were fixed with 4% paraformaldehyde and stained with Alizarin Red to assess the osteogenic differentiation effect.
[0052] Figure 3(B) shows the alizarin red staining of BMSCs treated with MF-LDH for 14 days in the control group (osteogenic differentiation culture medium only) and in Example 1 of this invention. The results show that MF-LDH treatment can deepen the positive staining of calcium nodules in alizarin red, and the MF-LDH group treatment can more effectively promote alizarin red staining for osteogenic differentiation.
[0053] Example 6: Real-time quantitative PCR detection of osteogenic differentiation gene expression BMSCs were seeded in 12-well plates at a density of 1×10⁵ / mL and cultured in medium at 37℃ and 5% CO₂ for 18–24 h until the cell confluence density reached 70% for subsequent material processing. The composition of the BMSC osteogenic differentiation medium was: MEM; 10% fetal bovine serum; 0.1 μmol / L dexamethasone; 20 μg / mL sodium anticortiate; 10 Mm β-glycerophosphate. LDH and MF-LDH solutions were prepared using the BMSC osteogenic differentiation medium to achieve a material concentration of 5 µg / mL in each group. After 7 and 14 days of differentiation, the changes in the gene expression levels of osteogenic differentiation genes BMP2, RunX2, and OPN in BMSCs after treatment were detected by real-time quantitative PCR, with Gapdh used as an internal control gene.
[0054] The specific primer sequences are as follows: Gapdh, upstream primer: GGTCGGTGTGAACGGATTTGG (SEQ ID NO.1), downstream primer: GCCGTGGGTAGAGTCATACTGGAAC (SEQ ID NO.2); BMP2, upstream primer: CCGAATTGGCTGAGTGTTCTGGT (SEQ ID NO.3), downstream primer: CTTGCGAGCTGTGTCTCCGTTT (SEQ ID NO.4); RunX2, upstream primer: CCATAACGGTCTTCACAAATCCT (SEQ ID NO.5), downstream primer: TCTGTCTGTGCCTTCTTGGTTC (SEQ ID NO.6). OPN, upstream primer: TTGGCTTTGCAGTCTCCTGCGG (SEQ ID NO.7), downstream primer: AGGCAAGGCCGAACAGGCAAA (SEQ ID NO.8).
[0055] Figure 4 This is a bar chart showing the gene expression levels of osteogenic differentiation genes BMP2, RunX2, and OPN in BMSC cells treated for 7 days using real-time quantitative PCR in the control group and the MF-LDH group of Example 1 of this invention. The horizontal axis represents different material treatments, and the vertical axis represents relative expression levels, with the relative expression level of the control group set to 1. Figure 4 It can be seen that, compared with the control group, the addition of MF-LDH treatment can promote the gene expression levels of osteogenic differentiation genes BMP2, RunX2 and OPN, indicating that the MF-LDH group has a good effect on promoting osteogenic differentiation of BMSCs.
[0056] Example 7: Contact and interaction between materials and cell surfaces Figure 5 This is a scanning electron microscope image showing the adhesion and spreading morphology of BMSC cells on the surface of the MF-LDH material. As can be seen from the image, the hollow rings of the MF-LDH framework are also in full contact with the cells, forming an efficient cell-material interaction interface, which further promotes cell adhesion and spreading.
[0057] Example 8: The role and effect of MF-LDH in Example 1 The framework MF-LDH prepared in Example 1, based on cell viability assays, alkaline phosphatase and alizarin red staining, and real-time quantitative PCR detection of pluripotent gene expression, shows that the framework MF-LDH can better promote osteogenic differentiation of BMSCs, effectively increase alkaline phosphatase and alizarin red staining, and upregulate the expression of osteogenic-related genes BMP2, RunX2, and OPN. Therefore, the MF-LDH prepared in Example 1 has the advantage of promoting osteogenic differentiation and has broad application prospects.
[0058] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention.
Claims
1. A magnesium ion-enriched framework layered bimetallic hydroxide material, characterized in that, The frame-layered bimetallic hydroxide material is a hollow crystalline material with independent hexagonal pores, and the morphology of the independent hexagonal pores is a single hexagonal unit in a honeycomb structure. The framework layered bimetallic hydroxide material is obtained by alkaline etching of conventional layered bimetallic hydroxides.
2. The magnesium ion-enriched framework layered bimetallic hydroxide material according to claim 1, characterized in that, The general formula of the traditional nanolayered double hydroxide is [M 2+ (1-x) M 3+ X [(OH)2]x+[An-]x / n·zH2O, where M 2+ It is a divalent metal cation, M 3+ A is a trivalent metal cation. n- M is an anion with an interlayer valence of n, X is the molar ratio of trivalent cations to all cations, z is the number of water molecules of crystallization between each nanolayered double hydroxide molecule, and M is the anion with an interlayer valence of n. 2+ and M 3+ The salts formed are all soluble; the M 2+ Mg 2+ The M 3+ For Al 3+ The A n- CO3 2- ; Mg in the material 2+ With Al 3+ The molar ratio is (1-x):x = 1:1 - 5:
1.
3. A method for preparing a magnesium ion-enriched framework layered bimetallic hydroxide material according to any one of claims 1-2, characterized in that, Includes the following steps: (1) Disperse traditional layered double hydroxide materials in water to prepare an LDH suspension of 1.0-2.5 mg / mL; (2) Prepare an alkaline solution of 0.5-2 mol / L using double-distilled water to remove CO2 as a solvent; (3) The LDH suspension obtained in step (1) and the alkaline solution are mixed at a ratio of 1.5-2 mg / mL between LDH and alkaline solution, and transferred to a hydrothermal synthesis reactor. The mixture is heated at 150-160℃ for 2-5 h to obtain the suspension. (4) After washing with deionized water three times, the suspension is then freeze-dried at -80°C or vacuum-dried at 37°C to obtain a magnesium ion-enriched framework layered bimetallic hydroxide material.
4. The method for preparing the magnesium ion-enriched framework layered bimetallic hydroxide material according to claim 3, characterized in that, The alkaline solution mentioned in step (3) is either a potassium hydroxide solution or a sodium hydroxide solution; the concentration of the alkaline solution is 1M.
5. The method for preparing the magnesium ion-enriched framework layered bimetallic hydroxide material according to claim 3, characterized in that, The traditional method for preparing layered double hydroxide materials includes the following steps: S1. Dissolve soluble divalent metal ion salts and soluble trivalent metal ion salts in water to prepare metal ion salt solutions; S2. Use double-distilled water (with CO2 removed) as a solvent to prepare a urea solution; S3, a mixed metal ion salt solution and a urea solution were transferred to a hydrothermal synthesis reactor and heated at 100°C for 24 h to obtain a suspension; S4. Dry the suspension to obtain a traditional layered double hydroxide.
6. The method for preparing the magnesium ion-enriched framework layered bimetallic hydroxide material according to claim 5, characterized in that, In step S1, the soluble divalent metal ion salt is selected from either magnesium nitrate or magnesium chloride; the soluble trivalent metal ion salt is selected from either aluminum nitrate or aluminum chloride. The molar ratio of divalent metal ion salt to trivalent metal ion salt in step S1 is 1:1 to 5:1; In step S3, the molar ratio of urea to metal ion salt solution is 3 to 5:
1.
7. The use of the magnesium ion-enriched framework layered bimetallic hydroxide material according to any one of claims 1-2 in the preparation of a drug that promotes osteogenic differentiation of mesenchymal stem cells.
8. The application according to claim 7, characterized in that, The mesenchymal stem cells mentioned are bone marrow-derived mesenchymal stem cells or osteoblastic progenitor cells.
9. The use of the magnesium ion-enriched framework layered bimetallic hydroxide material according to any one of claims 1-2 in the preparation of drugs for bone defect repair and regeneration.
10. The application according to claim 9, characterized in that, The amount of magnesium ion-enriched framework layered bimetallic hydroxide material added to the drug is 5-30 μg / mL.